2023
DOI: 10.1038/s41597-023-02215-x
|View full text |Cite
|
Sign up to set email alerts
|

ICESat-2 river surface slope (IRIS): A global reach-scale water surface slope dataset

Abstract: The global reach-scale “ICESat-2 River Surface Slope” (IRIS) dataset comprises average and extreme water surface slopes (WSS) derived from ICESat-2 observations between October 2018 and August 2022 as a supplement to 121,583 reaches from the “SWOT Mission River Database” (SWORD). To gain full advantage of ICESat-2’s unique measurement geometry with six parallel lidar beams, the WSS is determined across pairs of beams or along individual beams, depending on the intersection angle of spacecraft orbit and river c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Further, when compared with ICESat-2 slopes (05 sample points), bias (SWORD-ICESat-2) range and mean found to be -4.02 to 20.76 cm/km and 4.5 cm/km respectively. It is observed that, SWORD dataset showed relatively low agreement with GNSS and ICESat-2 data; obviously because of higher vertical accuracy of the ICESat-2 data compared to MERIT DEM [36]. Further, [36] compared ICESat-2 River Surface Slope (IRIS) with SWORD, and reported the bias range from -65.7cm/km to 477.4cm/km on basin scale (having reaches more than 5) with mean of 14.9 cm/km.…”
Section: ) Wss Using Icesat-2 Data For Sword River Reachesmentioning
confidence: 94%
See 3 more Smart Citations
“…Further, when compared with ICESat-2 slopes (05 sample points), bias (SWORD-ICESat-2) range and mean found to be -4.02 to 20.76 cm/km and 4.5 cm/km respectively. It is observed that, SWORD dataset showed relatively low agreement with GNSS and ICESat-2 data; obviously because of higher vertical accuracy of the ICESat-2 data compared to MERIT DEM [36]. Further, [36] compared ICESat-2 River Surface Slope (IRIS) with SWORD, and reported the bias range from -65.7cm/km to 477.4cm/km on basin scale (having reaches more than 5) with mean of 14.9 cm/km.…”
Section: ) Wss Using Icesat-2 Data For Sword River Reachesmentioning
confidence: 94%
“…It is observed that, SWORD dataset showed relatively low agreement with GNSS and ICESat-2 data; obviously because of higher vertical accuracy of the ICESat-2 data compared to MERIT DEM [36]. Further, [36] compared ICESat-2 River Surface Slope (IRIS) with SWORD, and reported the bias range from -65.7cm/km to 477.4cm/km on basin scale (having reaches more than 5) with mean of 14.9 cm/km. The proposed statistics unfolds the advantage and limitations of the SWORD WSS slope using available limited in-situ and satellite observations.…”
Section: ) Wss Using Icesat-2 Data For Sword River Reachesmentioning
confidence: 94%
See 2 more Smart Citations
“…The reach-scale "ICESat-2 River Surface Slope" (IRIS, Scherer et al, 2022bScherer et al, , 2023 data set is used to evaluate the results of this study. IRIS is derived for each SWORD (Version 15) reach (Altenau et al, 2021) from observations of the spaceborne lidar sensor ATLAS onboard ICESat-2.…”
Section: Icesat-2 River Surface Slopementioning
confidence: 99%